Evaluation for block-scale solar energy potential of industrial block and optimization of application strategies: A case study of Wuhan, China. (September 2021) - Xu, Shen; Jiang, Haihua; Xiong, Feng; Zhang, Chen; Xie, Mengju; Li, Zhixin
Highlights: Introduces an evaluation method of solar energy potential for industrial block. Single-storey industrial blocks have the largest total solar potential. Density has a significant impact on solar potential for industrial blocks. Roof has the highest effective installation rate, then South and West facade. Abstract: Industrial blocks are an important part of the city which is very suitable for PV application because of its large-scale, unified property rights and simple form. In this study, a multi-dimensional evaluation method of solar energy potential suitable for the block-scale is constructed. Then, 48 cases of industrial blocks in a typical city of china were selected as examples. Basing on morphological parameters, all cases were classified into 7 types by clustering algorithm. Afterwards, the total amount and distribution of the solar energy potential were calculated. Finally, the strategies of the photovoltaic system application in blocks were proposed according to types of blocks. It is found that there is significant difference in solar energy potential between different types of industrial blocks. Among them, solar energy potential of single-storey types is the highest up to 90.85 kW h/m 2 year, while solar energy potential of high-rise type blocks is relatively lower which is only 55.64 kW h/m 2 year. In addition, block shape has obvious impact on solar energy potential, among which building density having the greatest influence, as building density increases from 20 % to 55 %, the solar energy potential also increased by 138.74 % from 42.54 kW h/m 2 year to 101.56 kW h/m 2 year.